A Combined Hybrid Finite Element Method for Plate Bending Problems (Journal of Computational Mathematics, 2003)
In this paper, a combined hybrid method is applied to finite element discretization of plate bending problems. It is shown that the resultant schemes are stabilized, i.e., the convergence of the schemes is independent of inf-sup conditions and any other patch test. Based on this, two new series of plate elements are proposed.
Keywords: Combined hybrid finite element; Weakly compatible.